(untitled) (Revista Eletrônica: Tempo - Técnica - Território / Eletronic Magazine: Time - Technique - Territory, 2016)
A personal testimony and experienced of filmmaker Renato Barbieri in their relationship with the African continent, from the first connections in adolescence, through their film production and research trips. They are stories that go beyond intellectual knowledge and reach the field in the affective and aesthetic affinities and contrasts between Brazil and Africa.